Gender Determination by Linear Dimension of Permanent Canine: An Odontometric Analysis - Sharma, B; Balaji, N; Sumathi, MK (Janaki Medical College Journal of Medical Science, 2014)
Background and objectives: Identification, an aspect of forensic anthropology, is the recognition of an individual based on the physical characteristics unique to the individual. Among the four main attributes i.e. gender, age, stature and ethnic or racial background of an individual’s biological identity, sex determination is usually the first step in the human identification process. Teeth can be used as a means of sex determination as teeth are resistant to post-mortem degradation and survive deliberate, accidental or natural change. This study was carried out with an objective to determine the sexual dimorphism of maxillary and mandibular canine by linear tooth diameter for permanent dentition in Moradabad population. Material and Methods: A total number of 40 subjects (20 Males and 20 Females) were included in this study. After obtaining an informed written consent, alginate impression was taken with help of perforated impression trays and study models were prepared with type IV dental stone. Linear (MD, BL, Crown Height) were taken with digital vernier caliper. Results: It was observed that males’ shows more mean linear crown diameter as compared to females. Also, the mesiodistal and buccolingual measurement shows statistically significant difference for all canines, being higher for males than females. Conclusion: The present study has expressed sexual dimorphism of permanent canine using Student’s test and indicate that linear dimension of maxillary canine can be used for sexual diamorphism with accuracy along with other accepted procedure for sex determination. DOI: http://dx.doi.org/10.3126/jmcjms.v2i1.11392 Janaki Medical College Journal of Medical Sciences (2014) Vol. 2 (1): 23-27